2006
DOI: 10.1063/1.2386925
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of electrical transport from variable range hopping to hard gap resistance in Zn1−xFexO1−v magnetic semiconductor films

Abstract: Transformation of the electrical transport from the Efros and Shklovskii ͓J. Phys. C 8, L49 ͑1975͔͒ variable range hopping to the "hard gap" resistance was experimentally observed in a low temperature range as the Fe compositions in Zn 1−x Fe x O 1−v ferromagnetic semiconductor films increase. A universal form of the resistance versus temperature, i.e., ϰ exp͓T H / T + ͑T ES / T͒ 1/2 ͔, was theoretically established to describe the experimental transport phenomena by taking into account the electron-electron C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 27 publications
0
16
0
1
Order By: Relevance
“…Magnetic doped ZnO has attracted broad interests for their possible use as spintronic materials [10][11]. ZnO doped with transitional magnetic metal, such as Zn 1-x TM x O (TM=Mn, Fe, Co, and Ni) [12][13][14][15] were found to be diluted magnetic semiconductors with high Curie temperature. Some previous researchers reported that the inhomogeneous distribution of transitional metal might greatly influence the magnetic and electronic properties of the ZnO-based materials [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic doped ZnO has attracted broad interests for their possible use as spintronic materials [10][11]. ZnO doped with transitional magnetic metal, such as Zn 1-x TM x O (TM=Mn, Fe, Co, and Ni) [12][13][14][15] were found to be diluted magnetic semiconductors with high Curie temperature. Some previous researchers reported that the inhomogeneous distribution of transitional metal might greatly influence the magnetic and electronic properties of the ZnO-based materials [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…lnρ depends linearly on T −1/2 , suggesting that the Efros variable range hopping (VRH) may be the dominant conduction mechanism, meaning that Coulomb interactions between carriers dominate the electrical transport [61]. The hopping resistivity can be described as lnρ/ρ 0 = (T/T Ef ros ) −1/2 [19,61,62], where T Ef ros = 8e 2 /ε r k B ξ , ρ 0 is the resistivity coefficient, e is the electron charge, ε r is the dielectric constant [20], k B is the Boltzmann constant, and ξ is the localization length of carriers near the Fermi level. The VRH conduction mechanism and the small change of saturation magnetization at room and low temperatures suggest that bound magnetic polarons may be the origin of the ferromagnetism.…”
Section: Resultsmentioning
confidence: 99%
“…In the magnetic Anderson localization system, the localized carriers should be spin polarized, and can 'feel' not only the local electrical potential fluctuation but also the local magnetic potential fluctuation. In this system, electrical transport is caused by spin-dependent variable range hopping of the carriers from the initial localized occupied state to the final vacant state due to thermal activation [26,31]. It is believed that plentiful oxygen vacancies in Zn 0.32 Co 0.68 O 1−v magnetic semiconductor can produce dense discrete local energy levels near the Fermi level, which not only supply localized electrons for the variable range hopping transport, but also mediate the ferromagnetic interaction between Co atoms to form ferromagnetism in Zn 0.32 Co 0.68 O 1−v magnetic semiconductor [25,26].…”
Section: Concentrated Magnetic Semiconductor and The Above-gap Peaksmentioning
confidence: 99%